Mortality Information System (MorbIS): painel interativo para exibição de dados do sistema de informação sobre mortalidade do DATASUS - Sá Neto, Alessandro Pereira Torres de (2022)
We currently have multiple platforms for visualizing health data, where Tabnet being one of the main ones. With Tabnet, the user is able to consult and download data from the Informatics Department of the Unified Health System (DATASUS), so that one can carry out his own research, such as following the evolution of deaths from certain diseases in Brazil. In this work, our goal is to create an application capable of providing health data through practical surveys, and providing information about the data for each query carried out by the user, in a more intuitive and interactive interface than the available in the market. Several different computational resources were used and integrated to create the application, such as the R and SQL programming languages, RStudio and pgAdmin4 interfaces, and many packages in R, the main one being the Shiny package to create the application. With the main idea defined and all the aforementioned tools available, the Mortality Information System (MorbIS) was created, which can be accessed by all users through the link <http://morbis.estatistica.ccet.ufrn.br> to, in addition to researching DATASUS data, have multiple visualizations of this data available, with interactive plots and summary tables regarding the desired information.